If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9g-8g-g+2g+4g=12
We move all terms to the left:
9g-8g-g+2g+4g-(12)=0
We add all the numbers together, and all the variables
6g-12=0
We move all terms containing g to the left, all other terms to the right
6g=12
g=12/6
g=2
| 5x2−2=6x | | 12 = 3 4 x | | n/6+45=48 | | 3.) 3 = x 6 2 | | 12r+4r-12r+r=15 | | 12+7*r=r-6 | | 3m-11=-2m | | 19+5.50x=10+6.75x | | 5x2x=19 | | (h-37)4=8 | | x+8x+-5x=-12 | | h=50−5 | | 0.5n-3+12=45 | | t/4+40=48 | | -11x+3-7+x=6+5 | | 20+7c=-15 | | 10=x9 | | 19x+x-14x=6 | | 6r^2=7+2r | | 2-8u=-38 | | 1/2n-3+12=45 | | 7c+20=15 | | 9w-8w=12 | | 6^2=7+2r | | 3q+21-5q=7q-13 | | 8(x-6)+2=8x-46 | | u-u+5u-3u=14 | | -14*5*y=y*3 | | -6w+9=4w-21 | | 9x5-4+14=55 | | 14=6+4c | | -1/2x-7/2=8/4x-7 |